Functional polyaniline-assisted decoration of polystyrene microspheres with noble metal nanoparticles and their enhanced catalytic properties. (14th November 2016) - Li, Yunxing; Hu, Yuhua; Ye, Sunjie; Wu, Yan; Yang, Cheng; Wang, Likui
Abstract : A smart strategy is reported for depositing noble metal nanoparticles on polystyrene microspheres using a polyaniline coating as a functional linker. Abstract : The use of polystyrene (PS) microsphere modified by polyaniline (PANi) as a functional support for Au nanoparticles (NPs) is described herein. Specifically, a simple strategy, involving swelling followed by diffusion and interfacial polymerization of aniline monomer, was applied to fabricate the PS/PANi composite particles, independent of any surface treatments of the PS seed microspheres. At mildly acidic pH, the surface of PANi was enriched with positive charge, hence enabling the negatively charged Au NPs (stabilized by trisodium citrate) to be uniformly attached onto the PS/PANi composite particles via a simple electrostatic self-assembly approach. The prepared PS/PANi-Au composite particles exhibit high catalytic activity and superior reusability in the reduction of p -nitrophenol using NaBH4 . Notably, this type of self-assembly could not only effectively control the density of the supported Au NPs with different sizes but could also easily immobilize other noble metal (Ag, Pt, and Pd) NPs onto the surface of the PS/PANi composite particles. More significantly, in addition to providing anchoring sites for immobilizing noble metal NPs, the PANi coating also contributes to the higher catalytic activity of PS/PANi-Au composite particles due to the synergistic effect of PANi and Au NPs.